Visually Induced Roll Circular Vection: Do Effects of Stimulation Velocity Differ for Supine and Upright Participants? - Wang, Yixuan; Du, Bo; Wei, Yue; So, Richard H. Y. (Frontiers in Virtual Reality, 2021)
Visually induced circular vection (CV) has been the subject of a wide range of functional brain and behavioral research. Participants in MRI or PET studies on CV were mostly in a supine viewing position, while participants in behavioral studies on CV were mostly in an upright viewing position. This study examines the effects of viewing positions (upright and supine) on roll CV reported by 16 participants while watching random dots (92x60 degrees field-of-view) rotating at different angular velocities (2, 4, 8, 16, 32, 64 deg/s) for 30 seconds. Viewing positions affected roll CV durations differently depending on the stimulation velocities. At slower velocities (2, 4 and 8 deg/s), participants exhibited significantly longer roll CV sensations when they were sitting in an upright position as opposed to lying in a supine position. The onset of roll CV was also significantly earlier with participants in an upright position despite similar roll CV intensities in both viewing positions. Significant two-way interactions between effects of viewing positions and dot rotating velocities for some conditions were noted. Consistency between current findings and the hypothesis predicting a weaker roll CV in upright positions based upon perceived gravity by the otolith organs is discussed.